2021
DOI: 10.3389/fncel.2021.777738
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 S1 Protein Induces Endolysosome Dysfunction and Neuritic Dystrophy

Abstract: SARS-CoV-2 is the viral cause of the COVID-19 pandemic. Increasingly, significant neurological disorders have been associated with COVID-19. However, the pathogenesis of these neurological disorders remains unclear especially because only low or undetectable levels of SARS-CoV-2 have been reported in human brain specimens. Because SARS-CoV-2 S1 protein can be released from viral membranes, can cross the blood-brain barrier, and is present in brain cells including neurons, we tested the hypothesis that SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In testing the hypothesis that the S1 protein of SARS-CoV-2 can directly induce neuronal injury, Datta et al (Datta et al, 2021) demonstrated that the exogenous S1 protein leads to endolysosomal dysfunction and dystrophy of neurons. These processes can also disrupt the transport of synaptic vesicle precursors, lysosomes and autophagic components (Datta et al, 2021). The authors correctly suggested that S1 is involved in the high incidence of neurological and psychological manifestations of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In testing the hypothesis that the S1 protein of SARS-CoV-2 can directly induce neuronal injury, Datta et al (Datta et al, 2021) demonstrated that the exogenous S1 protein leads to endolysosomal dysfunction and dystrophy of neurons. These processes can also disrupt the transport of synaptic vesicle precursors, lysosomes and autophagic components (Datta et al, 2021). The authors correctly suggested that S1 is involved in the high incidence of neurological and psychological manifestations of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Erickson et al, 2021);(Datta et al, 2021). Also, cross-reactions of antibodies or T-cells that misidentify inner ear antigens as viruses are capable of causing damage as well (DiMauro et al, 2022).…”
mentioning
confidence: 99%
“…3 B, C), indicating heightened synaptic transmission and neuronal excitability. Despite the fact that whether SARS-CoV-2 spike protein increases or decreases neuronal activity is controversial (37)(38)(39)(40). this observation is noteworthy, as it suggests that the spike protein, when directly interacting with neurons, has the potential to amplify their responsiveness to incoming signals.…”
Section: Spike Protein Increases Microglia-dependent Field Epsps (Fep...mentioning
confidence: 99%
“…As described above, it is a matter of debate whether SARS-COV-2 can enter the brain, but several studies indicate that the SARS-CoV-2 S1 protein can be released from viral membranes, can cross the BBB, and is present in brain cells including neurons ( Meinhardt et al, 2021 ; Rhea et al, 2021 ; Petrovszki et al, 2022 ). Thus, Datta et al (2021) tested the hypothesis that SARS-CoV-2 S1 protein can directly induce neuronal injury. The latter authors found that the S1 protein accumulates in endolysosomes of human cortical neurons and induces aberrant endolysosome morphology and neuritic varicosities, which could contribute to the high incidence of neurological disorders associated with COVID-19.…”
Section: Mechanisms Of Seizures and Epilepsy Associated With Viral In...mentioning
confidence: 99%